THE ROLE OF SOCIO-CULTURAL IN RELATIONSHIP MARKETING: CASE FINDINGS ON FARMERS IN WEST JAVA - Ahmady, Muchlis; Sumarwan, Ujang; Suharjo, Budi; Maulana, Agus (European Scientific Journal, ESJ, 2013)
This paper studies the revelation of human relationships that drive the marketing activities of agricultural products, the producers (farmers and ranchers), collectors, dealers and the modern market, which focuses on the producers of agricultural products (vegetables, fruits and chicken pieces) in West Java Jakarta and surrounding areas, research only limited investigating the relationship between sellers and their suppliers, not the relationship between the seller (the traditional markets, modern market) with the end consumer. The research was conducted in West Java and Jakarta and its surrounding areas with the implementation in November 2010 to January 2011. Site selection is done on purpose (purposive) on the grounds in West Java and Jakarta and its surroundings have a sufficiency objects to be studied about the manufacturer, supplier and retailer for agricultural commodities. In this study involving 205 respondents as a source of information that consists of four business groups of the modern market by 18 respondents (8.79%), vegetables by 84 respondents (40.97%), and fruits totalling 50 respondents (24, 39%), and the chicken pieces as much as 53 respondents (25.85%). In data collection conducted through face-to-face interviews, each respondent was instrumental in accordance with its position in the business chain, such as manufacturer, suppliers or retailers. Especially for the respondent retailers, they are managers or management of a modern market primarily responsible for the procurement of commodities. Analytical methods to be used include Descriptive Analysis and Structural Equation Model (SEM). Descriptive analysis aims to obtain an overview of the characteristics of the respondent (respondent relations and behavioural profile of research). Processing is done using frequency analysis and cross tabulation analysis, while SEM is used to validate the built model. The results revealed that long-chain trading system that occurs not only because of economic factors alone, but discovered the existence of socio-cultural involvement in decision-making system of trading activity. Trading system that occurred more informal, in the sense that there are no rules as a guide, the factor of trust and commitment between actors trading system is crucial in encouraging the emergence of shared values that motivated the early emergence of cooperation. Performance of the three aspects will be the basis for decision-making as well as a selection for the establishment of longterm cooperation of mutual benefit both financially and socially. Future research should be pursued to investigate the direct influence of relational benefits for the trust, commitment and shared values. Therefore, this research theme will be more developed and interesting to do further research if there are other important factors that could affect the partnership.